(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article focuses on the family and its role in social development in the process of globalization in our country, the moral foundations of family relations and views and imaginations in this regard, as well as the reforms that are being carried out regarding the family today.